PENGARUH KINERJA LINGKUNGAN, DEWAN KOMISARIS, LEVERAGE, DAN POLITICAL VISIBILITY TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DI INDONESIA - Amaryllia Sari Kartika; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2020)
This study aims to test the factors that can affect corporate social responsibility disclosure. The dependent variable of this study is corporate social responsibility which is measured using GRI G-4 Standard. The independent variables of this study are environmental performance, the board of commissioner, leverage, and political visibility. Political visibility variable is proxied by company size and industry type. The population of this study are all of the manufacture companies listed in Indonesia Stock Exchange (BEI) in 2016-2018. This study used purposive sampling method. Total samples are 99 companies. The research model was tested using multiple regression. The result of analysis showed that the environmental performance, the board of commissioner, and company size which is a proxy of political visibility have significant impact on corporate social responsibility disclosure, while leverage and industry type which is a proxy of political visibility did not significantly affect the corporate social responsibility disclosure.